The Effect of Macroeconomic Variables on the Growth of Corporate Sukuk Issuance - Ulfah, Indar Fauziah; Yetmi, Yosi Safri; Khairunnisa, Indah (LPPM Universitas Terbuka, 2022)
Sukuk is a reliable instrument in obtaining medium-term financing sources with sharia principles. Many companies have started issuing Sukuk, seeing the opportunity for the majority of the Muslim population in Indonesia. The returns provided are relatively more profitable for investors. Still, in 2019 the COVID-19 pandemic began to have an impact on the economy. Macroeconomic variables caused people's purchasing power and investment interest to decline so that many companies began to experience difficulties both in terms of sales and capital. This study aims to analyze the effect of to analyze the effect of macroeconomic variables, namely the dollar exchange rate, inflation, money supply, and the BI Rate on Corporate Sukuk Issuance in Indonesia for the 2015-2020 period. The type of research used is quantitative associative with secondary data. The method for taking samples uses the purposive sampling method using specific criteria or considerations. The sample taken is corporate Sukuk in Indonesia. The analytical method used is quantitative analysis with an associative approach. Meanwhile, to answer the hypothesis using a linear regression test consisting of t-test and F test and test the coefficient of determination (R2). This study partially shows that the exchange rate has no significant effect on the Issuance of Corporate Sukuk in Indonesia. In contrast, Inflation, Money Supply, and the BI Rate significantly affect the Issuance of Corporate Sukuk in Indonesia. Meanwhile, simultaneously, the exchange rate, inflation, money supply, and the BI Rate significantly affect the Issuance of Corporate Sukuk in Indonesia. With a coefficient of determination of 94.9%.